Multimodal interactions in traditional foot reflexology - Chimeremeze, O.H. (Institute of Electrical and Electronics Engineers Inc., 2014)
The application of multimodal interactivity in HCI and VR avails a host of advantages which includes enhancement of realism and the achievement of interactivity that is relatively close or identical to the conventional human to human interactions. Visual and aural interactions have been widely applied in various domains ranging from mobile industry to medical field. In Virtual reality stress therapy application particularly in the proliferation development towards the virtualization of traditional foot reflexology therapy, little is understood on the visual and aural interactive nature of the therapy and to what extent they contribute in relaxation and stress relief. This paper presents a study that examines from both the patients' and practitioners' perspective, the visual and aural interactive nature in foot reflexology domain since the practices promote relaxation and stress relief. The study explored 2 traditional foot reflexology sessions; data were collected through audio recorded semi-structured interview, and was analyzed using content analysis. Results were compared with the existing haptic exploratory proceduResearch The study findings presented the visual and aural interactive nature involved from the patients' and practitioners' perspective. Implications for future research are also discussed. Â© 2014 IEEE.